ANALYSIS OF THE RELATIONSHIP BETWEEN THE LEVEL OF INDIVIDUALITY OF PHYSICAL POSSIBILITIES AND THE STATE OF PSYCHOLOGICAL COMFORT OF STUDENTS - Orlenko, Natalia; Deineko, Ihor; Velychenko, Mykolai; Rakitina, Tetiana (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2022)
The article presents the results of theoretical and practical analysis of the application of the test index "Comfort", compared with the criteria for assessing the physical condition of a student in the program "Physical Education and Self-Improvement" for free at the National Aviation University (NAU), students in their development. The purpose of the study is to theoretically and practically substantiate the aspect of development of first-year students of the period of both adaptive and quarantine in the "Red Zone. It was stated that these studies were conducted during 2021-2022, during the current quarantine in Ukraine. Using the method of testing, as a result of which factors were revealed that reveal both the physical state and the psychological state – against the background of physical activity of the subjects. Results. It was found that the indicators of the test-index "Comfort" indicate a depressed psychological state of students in quarantine, both adaptive and quarantine in the "Red Zone", which in turn has low self-esteem criteria. At that time, the results were much better for students who, under the influence of physical activity (training process) had the opportunity to participate in competitions, winning a certain result. At this stage, the formation of ideals of behavior, standards of courage. The results show that this period is easier to tolerate adolescents who are more likely to form an image that implies social success, sociability, athletic physique, self-control and willingness to take risks. It is concluded that the improvement of the system of physical education in the Free Economic Zone and the use of modern means contributes to the achievement and maintenance of high physical, mental and intellectual capacity of students and is an important component of professional education of future aviation professionals. The need for self-affirmation of young people in our time, can be realized either in organized teams, where the leader becomes a mentor, or in informal groups